Integration of ceramic membrane through 3D printing technology - Lim, Chin Hwa (2016)
In this paper, 3D printing technology was being presented for its compatibility with ceramic materials due to its competitive process in terms of cost and speed, especially for the small quantities production. There were four types of ceramic membrane samples used in this study, which differ in their powder particle sizes and membrane shapes. They were 72μ without hole (1a), 72μ with hole (1b), 133μ without hole (2a), and 133μ with hole (2b). This paper presents the research effort that focuses on integration of ceramic powder with 3D printing technology in order to produce an effective ceramic membrane and characterize them on its physical, structural, and functional properties. Sample 1 has small particle size that results in small open (0.806cm³) and closed porosity (0.808cm³), which causes a higher bulk density (1.362g/cm³) if compared with sample 2, which has the open porosity (0.919cm³), closed porosity(1.127cm³) and bulk density (1.351g/cm³). The smaller particle forms an interconnecting structure that can trap the water molecules and increases the water absorption. The water absoption was 36.67% in sample 1 higher than that (33.24%) for sample 2. The 3D printing produces a ceramic membrane with an inhomogeneous structure which cause a deviation in its filtration rate. However, the membrane hole shape enhances the filtration rate by more than 50%, which is from 107.4ml/min to 171.1ml/min. The filtration rate was decreased with the treatment duration from 1 to 5 minutes due to the accumulation of particulate matters. The ceramic membrane with hole (1b and 2b) can improve the decreasing of filtration rate by 64.85% to 70.64% for particle size between 72μ to 133μ. The cleaning of the membrane was characterize by spectra detected by EDX and it shows an effectiveness in order to remove the accumulation of the particular matters after the backwash process. Among the samples, the ceramic membrane 1b has a higher efficiency in terms of chemical oxygen demand (COD) and total suspended solid (TSS), which were achieved 98.33% reduction in COD and 46.15% in TSS.